Report on 38th Annual Convention and International Symposium of ISSAR held at Manuthy, Kerala from 6-8th Dec 2023. (The Indian Journal of Animal Reproduction, 2023)
The inauguration of 38th Annual Convention of ‘The Indian  Society for Study of Animal Reproduction’ (ISSAR) and  International Symposium on ‘Frontiers in Theriogenology:  Research and Practice’ was held on 6th December 2023 at 10  AM in the Golden Jubilee auditorium, College of Veterinary  and Animal Sciences, Mannuthy, Thrissur, Kerala. The  Chairman of the organizing committee, ISSAR 2023 and  Faculty Dean, CVAS, Mannuthy, Prof. (Dr.) K. Vijayakumar  welcomed the gathering. The programme was presided  over by Prof. (Dr.) Shiv Prasad, President, ISSAR and Prof.  (Dr.) M. Selvaraju, Gen. Secretary, ISSAR presented the  annual report. The symposium was inaugurated by the  chief guest Prof. (Dr.) Mohanan Kunnummal, Hon’ble  Vice- Chancellor, Kerala University of Health Sciences.  The guest of honour, Prof. (Dr.) M.R. Saseendranath,  Hon’ble Vice- Chancellor of Kerala Veterinary and Animal  Sciences University addressed the august gathering and  released the compendium. The former senior faculty  members of the Department of Animal Reproduction,  Gynaecology and Obstetrics, Kerala were honoured during  the occasion. Felicitations were offered by Prof. (Dr.) T.S.  Rajeev, Director of Entrepreneurship, KVASU and Dr. R.  Rajeev, Managing Director, Kerala Livestock Development  Board. Dr. C. Jayakumar, Organizing Secretary, ISSAR  2023 & Associate Professor and Head, Department of  ARGO, CVAS, Mannuthy offered vote of thanks. Dr. Brig.  N. M. Singhvi VSM and Dr. Sudhir Kumar Agarwal have  been awarded with Life Time Achievement Award 2022  and 2023 respectively. Dr. G. N. Purohit, Dr. Pankaj Sood,
Keywords: Annual Convention; (ISSAR); Research; Frontiers in Theriogenology